PSIKOEDUKASI PENGEMBANGAN KOMPETENSI INTI GURU SLB A DAN A+E JAKARTA - Handayani, Penny; Tunjungsari, Laurensia Harini; Fajri, Afrida Na’imatul Fajri; Asa, Maria D C; Safira, Nadilla (Jurnal Serina Abdimas, 2024)
SLB E is a private school that provides educational services to blind and multiple blind students, from elementary school, junior high school, and senior high school. With the complexity of the dynamics of educational services needed, teachers in this school still need to have sufficient pedagogical, professional, social, and personality competencies. This activity aims to develop teachers' core competencies including pedagogical, professional, social, and personality competencies of teachers in SLB E which will have an impact on their understanding of the characteristics of MDVI students, how to handle and educate MDVI students, how to communicate assertively between fellow teachers and how to cope with stress. The needs analysis was conducted through questionnaires, interviews, observations, and focus group discussions. Based on the results of the needs analysis, a psychoeducation program was developed that targets the ability to understand students, understand learning materials, socialize with colleagues, and have a steady, stable, wise, and authoritative personality. These abilities are related to the four core competencies of SLB teachers, namely pedagogical, professional, social, and personality competencies. Evaluation was conducted using qualitative and quantitative methods to see the effectiveness of the psychoeducation activities conducted during the two-day event. In general, there was an increase in teachers' understanding and knowledge of pedagogical, professional, social, and personality competencies. Follow-up activities were conducted several months after the activity to see the long-term effectiveness of the activity. ABSTRAK SLB E adalah sebuah sekolah swasta yang memberikan layanan pendidikan pada siswa tunanetra dan siswa tunanetra ganda, dari jenjang Sekolah Dasar (SD), Sekolah Menengah Pertama (SMP), dan Sekolah Menengah Atas (SMA). Dengan kompleksitas dinamika pelayanan pendidikan yang dibutuhkan, guru yang mengajar di sekolah ini masih belum memiliki kompetensi pedagogik, profesional, sosial dan kepribadian yang cukup memadai. Kegiatan ini bertujuan untuk mengembangkan kompetensi inti guru yang mencangkup kompetensi pedagogik, profesional, sosial dan kepribadian guru di SLB E yang akan berdampak pada pemahaman mereka akan karakteristik siswa MDVI, mengenai cara penanganan dan pendidikan siswa MDVI, cara berkomunikasi secara asertif antara sesama guru dan cara coping stress. Analisis kebutuhan dilakukan melalui kuesioner, wawancara, observasi, dan focus group discussion. Berdasarkan hasil analisis kebutuhan didapatkan disusunlah program psikoedukasi yang menyasar kemampuan memahami peserta didik, memahami akan materi pembelajaran, kemampuan sosialisasi dengan sesama rekan kerja dan memiliki kepribadian yang mantap, stabil, arif dan berwibawa. Kemampuan ini berkaitan dengan empat kompetensi inti guru SLB yaitu kompetensi pedagogik, profesional, sosial dan kepribadian. Evaluasi dilakukan dengan metode kualitatif dan kuantitatif guna melihat efektifitas kegiatan psikoedukasi yang dilakukan selama dua hari kegiatan. Secara umum, terdapat peningkatan pemahaman dan pengetahuan guru mengenai kompetensi pedagogik, profesional, sosial dan kepribadian. Kegiatan follow up dilakukan beberapa bulan pasca kegiatan guna melihat efektivitas jangka panjang dari kegiatan.